A note on subject clitics in Akan - Richard Campbell (Studies in African Linguistics, 1998)
This paper is concerned with the analysis of pronominal subject clitics (SCLs) in Akan within the Priniciples and Parameters framework of syntactic theory. Two kinds of analysis are considered: one, where the SCL is a true pronoun, generated in an argument position (the argument analysis); the other, where the SCL is an inflectional element residing in Infl, which identifies a null pronominal (pro) in subject position (the pro analysis). On the basis of the distribution of null objects in causative constructions, it is argued that the pro analysis provides a more elegant account of the facts of Akan than does the argument analysis. Akan is therefore analyzed as a pro-drop, or null subject, language, permitting null pronominal subjects under certain circumstances. Finally, possible implications for Universal Grammar are considered.